Experimental and Numerical Determination of the Aerodynamic Characteristics of a Cruise Missile Model - Wojciech MAŚLANKA (Doświadczalno-numeryczne wyznaczanie charakterystyk aerodynamicznych modelu pocisku manewrującego, 2024)
A model of a cruise missile was tested in symmetrical air flow in a low-speed wind tunnel of the Military University of Technology (Warsaw, Poland). A virtual model of the missile was developed, and the geometry of the computational domain was built in the CAD environment of the ANSYS computational software suite. The domain was discretised in the ANSYS Meshing application, creating a hybrid computational mesh. Boundary conditions were determined in the ANSYS Fluent application, and physical (turbulent compressible flow) and numerical models were selected. Calculations were performed for three different turbulence models – Spalart-Almaras, realizable k-ε, and SST k-ω – and the results were compared to find the model providing the best convergence with in-tunnel measurements.
Keywords: Charakterystyki aerodynamiczne modelu pocisku manewrującego